Antimycobacterial Potential Of Secondary Metabolites Of Actinobacteria From A Tropical Mangrove In Northern Peninsular Malaysia - Adanan, Norshamiera (2023)
Actinobacteria play a crucial role in discovery of new antibiotics for diseases with known antimicrobial resistance, such as multidrug-resistant tuberculosis (TB) caused by Mycobacterium tuberculosis (MTB), which is becoming a major impediment to TB control worldwide. In this study, novel actinobacterial secondary metabolites with antimicrobial potential against MTB surrogate organisms were isolated from tropical mangroves in the northern region of Peninsular Malaysia. The objectives of this study were to 1) isolate and screen for antimycobacterial-producing actinobacteria in sediment and water samples from mangrove environments, 2) conduct crude extract evaluation using tetrazolium microplate assay (TEMA), checkerboard assay and time-kill assay to determine minimum inhibition and bactericidal concentration (MIC, MBC) and fractional inhibition concentration index (FICI), and 3) identify compounds through gas chromatography mass spectrometry (GCMS) analysis. A total of 54 mangrove actinobacterial isolates were isolated from three mangrove environments in Balik Pulau, Pulau Pinang, and Merbok, Kedah from water and sediment samples of four sites: crab holes, rhizosphere area, undisturbed area, and disturbed area.